2022
DOI: 10.1155/2022/6971092
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Influencing Factors of Serum Stress Index and Prognosis of HICH Patients by Different Anesthesia Methods Combined with Small Bone Window Microsurgery

Abstract: In order to investigate the effects of sevoflurane on the serum stress index level and prognosis of patients with hypertensive cerebral hemorrhage (HICH) during small bone window microsurgery, a total of 102 HICH patients are selected for analysis. MAP values in both groups decreased significantly at T1 and T2 ( P < 0.05 ), and the changes in MAP and HR indexes in the sevoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…According to the pathogenesis of cerebral hemorrhage, some scholars believe that hematoma causes irreversible damage to peripheral nerves after 24 h, so early surgical removal of the hematoma can effectively improve the prognosis of patients. At present, surgical treatment is commonly used in the treatment of HICH, but there is still a great debate on the surgical treatment of HICH and the timing of the operation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the pathogenesis of cerebral hemorrhage, some scholars believe that hematoma causes irreversible damage to peripheral nerves after 24 h, so early surgical removal of the hematoma can effectively improve the prognosis of patients. At present, surgical treatment is commonly used in the treatment of HICH, but there is still a great debate on the surgical treatment of HICH and the timing of the operation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eyelid part muscle table damage on appearance brings bad influence to the patient, which will be more severe eyelid dysfunction in severe cases. It not only influences the patient's quality of life but also brings psychological shadow to patients [ 1 , 2 ]. Periocular skin tissue is soft and thin due to its particularity, which is difficult to repair [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%